Measuring Students’ Critical Thinking Ability by Adapting California Critical Thinking Skills Test to Primary School Students - Kurniasari, Yohana Rina; Setyaningsih, Yuliana (English Department FBS UNP, 2020)
This research aims to describe (1) the validity and reliability of the instruments adapted from the California Critical Thinking Skills Test and (2) its implementation to measure elementary schools students’ critical thinking skill in the Indonesian language learning. The research data were the scores obtained from the validity and reliability testing and from the implementation of the instrument to measure the students’ critical thinking skill, from class observation and interview with the teacher, which were analyzed using the descriptive statistics. The results are (1) the adapted instrument to measure students’ critical thinking skill has a quite high validity (in interpreting, analyzing, and regulating) and high validity (in concluding, evaluating, and explaining). The reliability testing shows that the instrument is highly reliable with a Cronbach’s alpha of 0.634; and (2) the implementation of the instrument shows that 5% of the students have a high critical thinking skill, 14% high, 45% medium, and 36% low. The degree of critical thinking skill is described respectively: interpreting (48%), analyzing (51%), concluding (14%), evaluating (45%), explaining (74%), and self-regulating (56%). Thus, intensive efforts to increase students’ critical thinking skill must be done through the Indonesian language learning.